Pengembangan Bahan Ajar Pada Materi Zat dan Wujudnya Berbasis Kemampuan Berfikir Kreatif Tingkat SMP - Anidom, Ahmad Juan; Hartini, Sri; Wati, Mustika (Universitas Lambung Mangkurat, 2015)
The reason of activities about the development of teaching material about substance and its formâs lesson with the principle of creative thinking ability for junior high school at class VII-A SMPN 15 Banjarmasin because creative thinking ability of students is to lack and the students are less able to understand the book package. The aims of this research are (1) describe the validity of the developed teaching material, (2) describes the creative thinking ability of students after they use developed teaching material, (3) describe the response of students to developed teaching material. The method of research activities is the research and development with ADDIE model development (Analysis, Design, Develop, Implement, and Evaluate). Techniques for collecting the data is used validation sheet, observation sheets, and questionnaires. Analysis data techniques are used validity of theoretical (logic), and calculation of average percentage based on predefined category. The results of activities showed that (1) developed teaching material in category very valid and can be used as learning media of substance and its formâs lesson, (2) creative thinking ability of students after they use the developed teaching material in category very good, (3) response of students to developed teaching material in category very good.Â Â